2019
DOI: 10.3390/foods8110525
|View full text |Cite
|
Sign up to set email alerts
|

Online Prediction of Physico-Chemical Quality Attributes of Beef Using Visible—Near-Infrared Spectroscopy and Chemometrics

Abstract: The potential of visible–near-infrared (Vis–NIR) spectroscopy to predict physico-chemical quality traits in 368 samples of bovine musculus longissimus thoracis et lumborum (LTL) was evaluated. A fibre-optic probe was applied on the exposed surface of the bovine carcass for the collection of spectra, including the neck and rump (1 h and 2 h post-mortem and after quartering, i.e., 24 h and 25 h post-mortem) and the boned-out LTL muscle (48 h and 49 h post-mortem). In parallel, reference analysis for physico-chem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
7
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 36 publications
(44 reference statements)
1
7
2
Order By: Relevance
“…There are several other recent studies on the accuracy of predicting meat characteristics using NIR spectroscopy [ 26 , 27 ]. The best results were obtained predicting the chemical composition of organic matter of meat and the color traits, whereas modest results were obtained for the other physical traits, such as drip and cooking losses and meat tenderness [ 13 , 28 , 29 , 30 ]. Although prediction of mineral content is mainly correlative in nature, several studies on NIRS predictions of minerals have been published in the field of food and agriculture [ 3 , 31 ].…”
Section: Resultsmentioning
confidence: 99%
“…There are several other recent studies on the accuracy of predicting meat characteristics using NIR spectroscopy [ 26 , 27 ]. The best results were obtained predicting the chemical composition of organic matter of meat and the color traits, whereas modest results were obtained for the other physical traits, such as drip and cooking losses and meat tenderness [ 13 , 28 , 29 , 30 ]. Although prediction of mineral content is mainly correlative in nature, several studies on NIRS predictions of minerals have been published in the field of food and agriculture [ 3 , 31 ].…”
Section: Resultsmentioning
confidence: 99%
“…There are currently many methods and tools applied to monitor and determine the quality and safety of different meat types (beef, pork, lamb, and chicken) such as WBSF (de Nadai Bonin et al, 2020), pH meter (Sahar et al, 2019), texture analyzer (Sujiwo et al, 2019), and HPLC F I G U R E 1 General illustration of e-nose system applied for meat quality detection (Lu et al, 2017). As a whole, chemical and instrumentation tests are very precise and well standardized; however, due to their cost and drudgery associated with their use, they are not suitable for modern and adaptive, large-scale meat facility where high throughput and scale is required, and quick feedback is desired.…”
Section: Chemical and Instrumentation Methodsmentioning
confidence: 99%
“…However, several studies reported low predictive ability (R 2 cv ≤ 0.29 or R 2 p ≤ 0.30) in beef, pork, and lamb meat at research laboratories or commercial abattoirs (Fiorentini et al, 2017;Andersen et al, 2018;Patel et al, 2021;Savoia et al, 2021); this is likely due to narrower ranges in pH values compared with the 2 above-mentioned studies. moderate NIRS predictability for beef L* (R 2 cv = 0.33 to 0.49 or R 2 p = 0.42 to 0.52), a* (R 2 cv = 0.07 to 0.32 or R 2 p = 0.52 to 0.71), and b* (R 2 cv = 0.19 to 0.39 or R 2 p = 0.35 to 0.63; Sahar et al, 2019;Patel et al, 2021;Savoia et al, 2021) as well as for pork L* (R 2 cv = 0.63), a* (R 2 cv = 0.72), and b* color values (R 2 cv = 0.65; Furtado et al, 2019). These differences among studies for NIRS predictability of color values could be partly due to instrument variations.…”
Section: Near Infrared Spectroscopymentioning
confidence: 99%